2015
DOI: 10.1016/j.otsr.2015.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Change in acetabular version after lumbar pedicle subtraction osteotomy to correct post-operative flat back: EOS® measurements of 38 acetabula

Abstract: Changing the sagittal spinal alignment modifies both the pelvic and the acetabular parameters. PSO significantly increases sacral slope, thus inducing anterior pelvic tilt with significant acetabular retroversion. The measurements obtained using sterEOS(®) showed good inter-observer and intra-observer reproducibility. To our knowledge, this is the first study of changes in acetabular version after PSO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…SHS patients, by contrast, may benefit from corrective spinal surgery before the hip replacement. 34 - 36 Patients with SHS usually present with a stiffer LPC, which makes those patients mainly ‘hip users’ in situations of aberrant functional acetabular orientation, 10 , 12 increasing the risk of edge-loading and articular impingement (on a native or prosthetic hip). In order to face this aberrant functional acetabular orientation and prevent those complications happening, it seems reasonable to first use a higher tolerance implant (larger diameter head, dual mobility) 25 and second, to determine a personalised cup orientation.…”
Section: Discussionmentioning
confidence: 99%
“…SHS patients, by contrast, may benefit from corrective spinal surgery before the hip replacement. 34 - 36 Patients with SHS usually present with a stiffer LPC, which makes those patients mainly ‘hip users’ in situations of aberrant functional acetabular orientation, 10 , 12 increasing the risk of edge-loading and articular impingement (on a native or prosthetic hip). In order to face this aberrant functional acetabular orientation and prevent those complications happening, it seems reasonable to first use a higher tolerance implant (larger diameter head, dual mobility) 25 and second, to determine a personalised cup orientation.…”
Section: Discussionmentioning
confidence: 99%
“…There were significant connections among spine, pelvis, and hip joints during position changes in healthy human beings 10 , 11 and patients with spine or hip joints disorders 33 , 34 , 35 . A previous study 16 demonstrated that sagittal acetabular version would change significantly after PSO at lumbar spine. Both SAA and PFA of patients in our study had significant changes ( P < 0.001) during surgery, and the PFA in the LLL group was much larger ( P = 0.02) at post‐operation.…”
Section: Discussionmentioning
confidence: 94%
“…There were kinds of operative procedures for the patients with variable symptoms respectively 2 , 15 , however, the procedure of long‐segments with instrumentation and fusion was an effective treatment for the patients suffered global spine imbalance. Furthermore, the procedure of long‐fusion with three‐column osteotomy would reconstruct spinal alignment and acetabular orientation more effectively 15 , 16 , which have always borne the greatest risk to both surgeons and patients alike 2 , 17 , 18 . Therefore, there have been plenty of studies on surgical procedure of long‐fusion without advanced osteotomy for DSD patients 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations